Analysis of Three-Dimensional Scar Architecture and Conducting Channels by High-Resolution Contrast-Enhanced Cardiac Magnetic Resonance Imaging in Chagas Heart Disease - Santos,João Bosco de Figueiredo (2022)
ABSTRACT Background: We aimed to describe the morphology of the border zone of viable myocardium surrounded by scarring in patients with Chagas heart disease and study their association with clinical events. Methods: Adult patients with Chagas heart disease (n=22; 55% females; 65.5 years, SD 10.1) were included. Patients underwent high-resolution contrast-enhanced cardiac magnetic resonance using myocardial delayed enhancement with postprocessing analysis to identify the core scar area and border zone channels number, mass, and length. The association between border zone channel parameters and the combined end-point (cardiovascular mortality or internal cardiac defibrillator implantation) was tested by multivariable Cox proportional hazard regression analyses. The significance level was set at 0.05. Data are presented as the mean (standard deviation [SD]) or median (interquartile range). Results: A total of 44 border zone channels (1[1-3] per patient) were identified. The border zone channel mass per patient was 1.25 (0.48-4.39) g, and the extension in layers of the border zone channels per patient was 2.4 (1.0-4.25). Most border zone channels were identified in the midwall location. Six patients presented the studied end-point during a mean follow-up of 4.9 years (SD 1.6). Border zone channel extension in layers was associated with the studied end-point independent from left ventricular ejection fraction or fibrosis mass (HR=2.03; 95% CI 1.15-3.60). Conclusions: High-resolution contrast-enhanced cardiac magnetic resonance can identify border zone channels in patients with Chagas heart disease. Moreover, border zone channel extension was independently associated with clinical events.